Bảo quản số trong các thư viện và cơ quan lưu trữ - Lê, Bá Lâm (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
This article introduces digital preservation is the issue which is concerned in libraries and archives; Analysis, illustration The Open Archival Information System (OAIS) models and elements about Management-Technology-Content for successfully built a digital preservation project and finish article presents challenges and strategies in digital preservation.